The dynamics of domestic abuse and drug and alcohol dependency - Gadd, David (The British journal of criminology, 2019)
This article elucidates the dynamics that occur in relationships where there have been both substance use and domestic abuse. It draws interpretively on in-depth qualitative interviews with male perpetrators and their current and former partners. These interviews were undertaken for the National Institute for Health Research-funded ADVANCE programme. The article’s analysis highlights the diverse ways in which domestic abuse by substance-using male partners is compounded for women who have never been substance dependent, women who have formerly been substance dependent and women who are currently substance dependent. The criminological implications of the competing models of change deployed in drug treatment and domestic violence intervention are discussed alongside the policy and practice challenges entailed in reconciling them within intervention contexts where specialist service provision has been scaled back and victims navigate pressures to stay with perpetrators while they undergo treatment alongside the threat of sanction should they seek protection from the police and courts.